Public reporting of outcomes in radiation oncology: the National Prostate Cancer Audit. Issue 5 (May 2021) - Aggarwal, Ajay; Nossiter, Julie; Parry, Matthew; Sujenthiran, Arunan; Zietman, Anthony; Clarke, Noel; Payne, Heather; van der Meulen, Jan
Summary: The public reporting of patient outcomes is crucial for quality improvement and informing patient choice. However, outcome reporting in radiotherapy, despite being a major component of cancer control, is extremely sparse globally. Public reporting has many challenges, including difficulties in defining meaningful measures of treatment quality, limitations in data infrastructure, and fragmented health insurance schemes. The National Prostate Cancer Audit (NPCA), done in the England and Wales National Health Service (NHS), shows that it is feasible to develop outcome indicators for radiotherapy treatment, including patient-reported outcomes. The NPCA provides a transparent mechanism for comparing the performance of all NHS providers, with results accessible to patients, providers, and policy makers. Using the NPCA as a case study, we discuss the development of a radiotherapy-outcomes reporting programme, its impact and future potential, and the challenges and opportunities to develop this approach across other tumour types and in different health systems.